2020
DOI: 10.3390/antib9010004
|View full text |Cite
|
Sign up to set email alerts
|

Equal Neutralization Potency of Antibodies Raised against Abrin Subunits

Abstract: Abrin and ricin are potent AB toxins, which are considered biological threats. To date, there are no approved treatments against abrin or ricin intoxications. Previously, we showed that the administration of polyclonal anti-abrin antibodies to mice that were intranasally exposed to abrin, even very late post-exposure, conferred an exceedingly high-level of protection, while following ricin intoxication, similar treatment with anti-ricin antibodies resulted in negligible survival rates. To probe this unexpected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In sharp contrast, the administration of polyclonal anti-abrin antibodies to mice intranasally exposed to a lethal dose of abrin led to very high survival rates (~70-80%), even when the antibodies were applied as late as 72 h after intoxication [22]. This efficient protection by polyclonal anti-abrin antibodies could not be attributed to the neutralization of a single subunit because specific antibodies against the A or B subunits of abrin were equally effective in protecting mice against pulmonary intoxication with chimeric reciprocal toxins harboring one of the subunits of abrin and the other of ricin [24]. These observations indicated that the difference in the protection conferred by anti-abrin and anti-ricin antibodies against abrin and ricin intoxications, respectively, is not related to the difference in the quality of the two antibody preparations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sharp contrast, the administration of polyclonal anti-abrin antibodies to mice intranasally exposed to a lethal dose of abrin led to very high survival rates (~70-80%), even when the antibodies were applied as late as 72 h after intoxication [22]. This efficient protection by polyclonal anti-abrin antibodies could not be attributed to the neutralization of a single subunit because specific antibodies against the A or B subunits of abrin were equally effective in protecting mice against pulmonary intoxication with chimeric reciprocal toxins harboring one of the subunits of abrin and the other of ricin [24]. These observations indicated that the difference in the protection conferred by anti-abrin and anti-ricin antibodies against abrin and ricin intoxications, respectively, is not related to the difference in the quality of the two antibody preparations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the intranasal administration of polyclonal anti-abrin antibodies to mice even as late as 72 h postexposure to a lethal dose of abrin conferred exceedingly high-level protection [23]. Interestingly, the efficient protection by polyclonal anti-abrin antibodies cannot be attributed to the specific neutralization of a particular A or B subunit of the toxin, as antibodies raised against chimeric toxins of either an A abrin B ricin or A ricin B abrin structure conferred exceptionally high protection levels to mice following intranasal exposure to a lethal dose of abrin [24].…”
Section: Introductionmentioning
confidence: 99%
“…Many severe abrin poisoning cases and even death have been reported due to accidental and intentional abrin poisoning through ingestion, inhalation, and injection [ 14 ]. Currently, treatment for abrin poisoning is symptomatic, and there are no approved antidotes against abrin intoxications [ 15 ]. Neutralizing antibodies are known as a specific and effective strategy against biotoxin poisoning.…”
Section: Introductionmentioning
confidence: 99%